(untitled) (Medicine Anthropology Theory, 2020)
In this Photo Essay, photographs are combined with drawings collected in Burkina Faso in the years following the 2014–2016 Ebola outbreak. Portraits of bats are shown. The blacklisting of these animals following the recommendations of health authorities collides with local realities, where it is not possible to talk about bats in a ‘general’ sense. The same is true today in the period of COVID-19, when chiropterans are once again in the etiological hot seat: bats are behind the pandemic, according to Ridley’s shock phrase (2020). In Burkina Faso’s Lobi country, between the red and black fruit-eaters (which have always been eaten) and the small insectivores (which have never been eaten as such, but are very useful to animist healers), there is a chasm of representation that is unveiled by these images.